Reasons for school dropouts in suburban areas near Villupuram district: A retrospective study - D. Arthi; M. Rajalakshmi; Kalaiselvan Ganapathy (Journal of Current Research in Scientific Medicine)
Background: When a student leaves school or a college before completing their academic program, they are referred to as dropouts. A school dropout is anyone who does not receive their high school diploma. It is a serious issue that impacts students all over and can have negative outcomes in their lives. In general, those who struggle to engage behaviorally and/or academically drop out of school. Hence, we have chosen this study to find various reasons behind student dropouts in sub-urban areas of schools covered under Koliyanur block, Villupuram district. The objectives of this study were to determine the proportion and reasons for dropouts among school students in Koliyanur block, Villupuram district. Materials and Methods: It was a record-based retrospective study done among school students (1st–12th standard) who dropped out of school in July 2022. The secondary data on school dropouts (government and private) in the Koliyanur block of Villupuram district were obtained from the Chief Educational Officer of Villupuram. Out of 148 government and private schools, 36 schools had dropouts which were included in the study. Results: The prevalence of school dropouts among 36 schools was found to be 64 students. Migration, lack of interest, poverty, and lack of awareness remained the most common causes of dropouts in government schools, and fees not paid being the reason in private schools. Conclusion: Evidence generated from this study can aid education planners in the early identification of various reasons for school dropouts and take appropriate measures for their reduction.